The Effects of Regulatory Tools on Organizational Populations - Wholey, Douglas R.; Sanchez, Susan M. (Academy of Management Review, 1991)
One of the main activities of regulation is the control of market development by influencing the number of firms in an industry, their entry into an industry, and their exit from an industry. Population ecology is used as a framework for explaining both the direct and indirect effects of regulatory activity on entry, exit, and market structure. This framework is then used to derive specific propositions about regulatory effects on entry, exit, and market structure in the health maintenance organization industry.